Phosphorus rather than nitrogen regulates ecosystem carbon dynamics after permafrost thaw. (26th August 2021) - Yang, Guibiao; Peng, Yunfeng; Abbott, Benjamin W.; Biasi, Christina; Wei, Bin; Zhang, Dianye; Wang, Jun; Yu, Jianchun; Li, Fei; Wang, Guanqin; Kou, Dan; Liu, Futing; et al.
Abstract: Ecosystem carbon (C) dynamics after permafrost thaw depends on more than just climate change since soil nutrient status may also impact ecosystem C balance. It has been advocated that nitrogen (N) release upon permafrost thaw could promote plant growth and thus offset soil C loss. However, compared with the widely accepted C‐N interactions, little is known about the potential role of soil phosphorus (P) availability. We combined 3‐year field observations along a thaw sequence (constituted by four thaw stages, i.e., non‐collapse and 5, 14, and 22 years since collapse) with an in‐situ fertilization experiment (included N and P additions at the level of 10 g N m −2 year −1 and 10 g P m −2 year −1 ) to evaluate ecosystem C‐nutrient interactions upon permafrost thaw. We found that changes in soil P availability rather than N availability played an important role in regulating gross primary productivity and net ecosystem productivity along the thaw sequence. The fertilization experiment confirmed that P addition had stronger effects on plant growth than N addition in this permafrost ecosystem. These two lines of evidence highlight the crucial role of soil P availability in altering the trajectory of permafrost C cycle under climate warming. Abstract : Ecosystem carbon (C) dynamics after permafrost thaw could be impacted by soil nutrient status. However, current understanding of C‐nutrient interactions in permafrost ecosystems concentrates on nitrogen (N), little is known about the potential role of phosphorus (P) in mediating ecosystem C dynamics upon permafrost thaw. Based on the combination of 3‐year field observations along a permafrost thaw sequence with an in‐situ fertilization experiment, this study provided empirical evidence that soil P rather than N availability regulates ecosystem C dynamics after permafrost thaw, highlighting the key role of P in regulating the future trajectory of permafrost C cycle.